Genome editing a mouse locus encoding a variant histone, H3.3B, to report on its expression in live animals. Issue 12 (6th October 2014) - Wen, Duancheng; Noh, Kyung‐Min; Goldberg, Aaron D.; Allis, C. David; Rosenwaks, Zev; Rafii, Shahin; Banaszynski, Laura A.
Summary Chromatin remodeling via incorporation of histone variants plays a key role in the regulation of embryonic development. The histone variant H3.3 has been associated with a number of early events including formation of the paternal pronucleus upon fertilization. The small number of amino acid differences between H3.3 and its canonical counterparts (H3.1 and H3.2) has limited studies of the developmental significance of H3.3 deposition into chromatin due to difficulties in distinguishing the H3 isoforms. To this end, we used zinc‐finger nuclease (ZFN) mediated gene editing to introduce a small C‐terminal hemagglutinin (HA) tag to the endogenous H3.3B locus in mouse embryonic stem cells (ESCs), along with an internal ribosome entry site (IRES) and a separately translated fluorescent reporter of expression. This system will allow detection of expression driven by the reporter in cells, animals, and embryos, and will facilitate investigation of differential roles of paternal and maternal H3.3 protein during embryogenesis that would not be possible using variant‐specific antibodies. Further, the ability to monitor endogenous H3.3 protein in various cell lineages will enhance our understanding of the dynamics of this histone variant over the course of development. genesis 52:959–966, 2014. © 2014 Wiley Periodicals, Inc.